Patogênese de infecções de corrente sanguínea relacionada ao cateter venoso central por Staphylococcus epidermidis em neonatos críticos - Queiroz, Lícia Ludendorff (2019)
Introduction: The hospital bloodstream infeccions (BSI) are responsible for significant frenquencies of morbidity and mortality in Neonatal Intensive Care Units (NICU), resulting in prolonged hospitalization and increased costs, especially in low birth weight infants. Objective:The present study proposed to determine the pathogenesis of catheter-related bloodstream infections (CR-BSI) caused by Staphylococcus epidermidis using the PFGE technique ("Pulsed Field Gel Electrophoresis ") as well as to evaluate the risk factors for mortality among neonates with weights ≤ 1500 grams and > 1500 grams. Methods: The study included neonates from the ICU of Hospital de Federal University of Uberlândia during the period from October 2010 to August 2012. For the study of the pathogenesis, were used samples of S. epidermidis recovered from blood, skin at the insertion site, hub, as well as the mucosa of the nostril and gut, from 48 hours to 14 days after the use of the Catheter or until obtaining a positive culture for S. epidermidis and catheter tip obtained after removal. In addition, were determined the risk factors for the development of BSI caused by S. epidermidis using case study x paired control. In addition to verifying the presence of mecA genes and ACME (Arginine Catabolic Mobile Element) by polymerase chain reaction (PCR), in S.epidermidis. Results: In total, 125 neonates developed BSI (27.0%), with 98 (78.4%) defined as hospital-type, totaling 124 episodes. Sepsis preterm affected 20% of newborns with BSI with 48% mortality, mainly in neonates weighing ≤ 1500 grams. The presence of mechanical ventilation and clinical sepsis were the factors associated with mortality among the heaviest neonates. In the case study x paired control, all variables analyzed [Hospitalization time (P <0.0001), time of mechanical ventilation (P = 0.0003), parenteral nutrition time (P <0.0001), CVC use time (P <0.0001) and use of antibiotics (P <0.0001), except CVC use were significant by univariate analysis. From the total of 53 samples tested in the PCR, 67.9% were positive for the mecA gene (oxacillin resistant) with higher frequency between the samples of mucosa 39.9%. Only 7.6% of the samples had genes for ACME (characterized as ACME type II), 17% associated with skin. Among 19 cases of primary BSI, the origin of the infection was identified in only 36.8% of the cases, where two were characterized as definitive intraluminal, one definitive extraluminal and four had the origin from the mucous membranes, defined as translocation. In the majority (63.2%) of the cases the origin of the infection could not be determined. The cross-transmission was a frequent event observed in the Unit. Conclusion: Despite the clinical and epidemiological importance of the BSI in the critical neonates and the magnitude of the study, in the majority of cases it was not possible to determine the origin of the microorganism present in the blood and although it has been observed high clonal diversity among the S. epidermidis samples, the cross-transmission was a common event.